Emission mechanism for the silicon He-α lines in a photoionization experiment. (11th February 2021) - Han, Bo; Wang, Feilu; Salzmann, David; Zhong, Jiayong; Zhao, Gang
Abstract: In this paper, we present a reanalysis of the silicon He- $α$ X-ray spectrum emission in Fujioka et al .'s 2009 photoionization experiment. The computations were performed with our radiative-collisional code, RCF. The central ingredients of our computations are accurate atomic data, inclusion of satellite lines from doubly excited states and accounting for the reabsorption of the emitted photons on their way to the spectrometer. With all these elements included, the simulated spectrum turns out to be in good agreement with the experimental spectrum.